Impact of Human Development Index on the profile and outcomes of patients with acute coronary syndrome. Issue 4 (23rd December 2014) - Roy, Ambuj; Roe, Matthew T; Neely, Megan L; Cyr, Derek D; Zamoryakhin, Dmitry; Fox, Keith A A; White, Harvey D; Armstrong, Paul W; Ohman, E Magnus; Prabhakaran, Dorairaj
Abstract : Objective: To study the impact of national economic and human development status on patient profiles and outcomes in the setting of acute coronary syndrome (ACS). Methods: We conducted a retrospective analysis of the Targeted Platelet Inhibition to Clarify the Optimal Strategy to Medically Manage Acute Coronary Syndromes trial (TRILOGY ACS) population (51 countries; 9301 patients). Outcome measures compared baseline characteristics and clinical outcomes through 30 months by 2010 country-level United Nations Human Development Indices (HDIs) and per-capita gross national income. Results: TRILOGY ACS enrolled 3659 patients from 27 very-high HDI countries, 3744 from 18 high-HDI countries and 1898 from 6 medium-HDI countries. Baseline characteristics of groups varied significantly, with the medium-HDI group having a lower mean age (63.0 years, vs 65.0 and 68.0 years for high-HDI and very-high HDI, respectively; p<0.001), lower baseline Global Registry of Acute Coronary Events risk score and lower rate of non-ST-segment elevation myocardial infarction (58.0%, vs 62.2% and 83.9% among high-HDI and very-high HDI, respectively). Medium-HDI and high-HDI patients had lower unadjusted 30-month rates for the composite of cardiovascular death/myocardial infarction/stroke (17.6%, 16.9% and 23.1% for medium-HDI, high-HDI and very-high HDI, respectively); this difference disappeared after adjusting for baseline characteristics. Adjusted HRs for the composite endpoint were lower in lower-income/middle-income countries vs upper-income/middle-income (0.791(95% CI 0.632 to 0.990)) and high-income countries (0.756 (95% CI 0.616 to 0.928)), with differences largely attributable to myocardial infarction rates. Conclusions: Clinical patient profiles differed substantially by country HDI groupings. Lower unadjusted event rates in medium-HDI countries may be explained by younger age and lower comorbidity burden among these countries' patients. This heterogeneity in patient recruitment across country HDI groupings may have important implications for future global ACS trial design. Trial registration number: NCT00699998.